Socially distanced activism : voices of lived experience of poverty during COVID-19 - Goldstraw, Katy (Rapid response., 2021)
How would your experience of the COVID-19 pandemic have been different if you had no access to the internet? The APLE Collective - a group seeking to eradicate poverty - rooted their pandemic activism in expertise held by those with lived experience of poverty. This resulted in the decision to campaign against the exclusively digital response to the crisis and the alienation of people in poverty. Drawing on case studies from Thrive Teeside, ATD Fourth World and Expert Citizens (APLE Collective organisations), this book interrogates the term 'lived experience'. It critically investigates how knowledge gained from lived experiences of poverty is integral to developing effective COVID-19 policy responses.